Luminescence properties and energy transfer in Ce3+/Tb3+co–doped Y5Si3O12N oxynitride phosphors. (January 2019) - Khan, Sayed Ali; Khan, Noor Zamin; Ji, Wei Wei; Ali, Liaqat; Abadikhah, Hamidreza; Hao, Luyuan; Xu, Xin; Agathopoulos, Simeon; Khan, Qasim; Zhu, Ling
Abstract: A series of Y5 Si3 O12 N:Ce 3+ single-doped and Ce 3+ /Tb 3+ co–doped phosphors, as potential candidates for application in tri–chromatic white LEDs, were successfully synthesized by a high temperature solid state reaction method. The addition of Li2 CO3 flux (5 wt%) improved the purity of the resultant phosphors and increased their emission intensity. An intense, broad excitation band in the range of 200–400 nm with a peak at 358 nm was recorded, which suits the needs of UV LED chips. Under this excitation wavelength, intense blue emission, which peaked at 439 nm, was recorded in the Ce 3+ single-doped phosphors, while two distinct luminescence bands were observed in the Ce 3+ /Tb 3+ co–doped Y5 Si3 O12 N phosphors: a blue one, which peaked at 439 nm and is ascribed to Ce 3+ ions, and an efficient green one, which peaked at 549 nm and is assigned to 5 D4 → 7 F5 transitions in Tb 3+ ions. A high luminescence quantum yield, of 85%, was achieved. The experimental results illustrate that efficient energy transfer can take place from the sensitizer Ce 3+ ions to the activator Tb 3+ ions in the Ce 3+ /Tb 3+ co–doped Y5 Si3 O12 N phosphors, through predominantly dipole–dipole interactions. Highlights: Purity and emission intensity of the prepared phosphors are improved with flux addition. Broad excitation band having maximum peak at 358 nm suits the needs of UV LED chips. A high luminescence quantum yield, of 85%, was achieved. The intensity of the emission at 150 °C is 80% of the intensity at room temperature.